Pengembangan Media R-Geo Berbasis Android Terhadap Pemahaman Konsep dan Minat Belajar Siswa pada Materi Rotasi - Lola Aulia Rizqi; Farid Gunadi; Wiwit Damayanti Lestari (Venn: Journal of Sustainable Innovation on Education, Mathematics and Natural Sciences, 2025)
The difficulties experienced by students in learning geometric rotation material generally stem from their limited conceptual understanding and the lack of engaging, interactive learning media. These challenges lead to low conceptual comprehension and suboptimal learning outcomes. Therefore, an innovative solution is required through the development of technology-based learning applications capable of presenting material sequentially, visually, and interactively. This study aims to develop, determine the feasibility, practicality, and effectiveness of Android-based R-Geo learning media to enhance students’ conceptual understanding and interest in geometric rotation topics at the high school level. The research employed the Research and Development (R&D) method with the 4D model (Define, Design, Develop, Disseminate). The feasibility of the R-Geo media was analyzed using the chi-squared technique, while practicality was assessed through student questionnaires and teacher observation sheets. The effectiveness test involved normality analysis using the Shapiro-Wilk test, followed by a one-shot t-test to examine significant differences after implementation. The results showed that R-Geo media met the criteria of being feasible, practical, and effective in supporting geometry learning. The media provides an interactive and appealing learning experience, enabling teachers to explain rotation concepts more dynamically and visually. Consequently, R-Geo can strengthen students’ comprehension of abstract rotation concepts and foster higher learning engagement. It is recommended that teachers integrate Android-based R-Geo media with various learning strategies to optimize learning outcomes and enhance student motivation in studying geometry.